2011
DOI: 10.3109/0142159x.2010.530319
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of medical students’ self-reported empathy with simulated patients’ assessments of the students’ empathy

Abstract: While significant associations exist between students' self-reported scores on the JSPE and SPs' evaluations of students' empathy, the associations are not large enough to conclude that the two evaluations are redundant.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
63
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
5
3
1

Relationship

4
5

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 15 publications
4
63
0
4
Order By: Relevance
“…High influencers also received significantly higher scores from the ''patients'' during their simulated patient experiences. Similar findings are reported by Berg et al (2011) who found that medical students with higher interpersonal skills (reflected in their scores on the JSE) received higher ratings of competence by simulated patients. It is important to note that whereas empathy scores for this specific study were assessed at matriculation, the simulated patient assessments were conducted during the students' third year.…”
Section: Demographics and Academic Performance Differencessupporting
confidence: 88%
“…High influencers also received significantly higher scores from the ''patients'' during their simulated patient experiences. Similar findings are reported by Berg et al (2011) who found that medical students with higher interpersonal skills (reflected in their scores on the JSE) received higher ratings of competence by simulated patients. It is important to note that whereas empathy scores for this specific study were assessed at matriculation, the simulated patient assessments were conducted during the students' third year.…”
Section: Demographics and Academic Performance Differencessupporting
confidence: 88%
“…In a study of 248 third year medical students, scores on the JSPPPE assessed by 10 simulated patients in the objective structured clinical examination (OSCE) stations were significantly correlated ( r = .87, P < .01) with the simulated patients’ global ratings of students’ empathy and support (28). …”
Section: Criterion-related Validitymentioning
confidence: 99%
“…Also, significant associations were observed between students’ JSE scores and ratings of clinical competence given by standardized patients in 10 Objective Structured Clinical Examination (OSCE) stations (Berg et al 2011, 2015). …”
Section: Introductionmentioning
confidence: 99%